Некоторые обратные задачи для уравнения теплопроводности с нелокальными краевыми условиями - Иванчов, Н.И. (Український математичний журнал, 1993)
Conditions under which the time-dependent temperature conductivity coefficient is determined uniquely are established in the case where the boundary conditions and the overdetermination conditions are non local.